Saan na po ang Olongapon ; Ad ban ; Leap of faith [videorecording] - Lazaro, Cheche (The Probe Team, 1992)
Tackles the situation of Olongapo residents after the pull-out of American military base; COMELEC ban on political advertisements; Kenny Loggins concert in Manila and interview about his philosophy and inspiration in life.